The struggle between equity and efficiency: Do nordic countries have a free lunch? - Norbert Berthold; Alexander B. Brunner (Luxembourg Income Study (LIS), 2008)
Although there is a vast theoretical literature on the existence of a tradeoff between equity and efficiency, empirical investigations often fail to find evidence for this proposition. Furthermore there are hints that some social models in Europe can cope better with this trade-off and are actually able to provide what economists call a 'free lunch'. In this paper we use data from the Luxembourg Income Studies (LIS) to evaluate (a) whether there really exists something like a free lunch and (b) whether some social systems are actually better in coping with the trade-off between equity and efficiency. – – Obwohl in der theoretischen Literatur die Existenz eines Trade-Offs zwischen Effizienz und Gerechtigkeit deutlich bejaht wird, ist dieser in der Empirie nur schwierig zu finden. Darüber hinaus scheint der Trade-Off von den verschiedenen europäischen Sozialmodellen unterschiedlich gut bewältigt zu werden. In einigen Ländern scheint sogar kein Trade-Off zu bestehen, so dass die Vermutung besteht, dass ein 'free lunch' existiert. In diesem Paper nutzen wir Daten der Luxembourg Income Studies (LIS) um empirisch zu evaluieren, ob (a) tatsächlich ein 'free lunch' existiert und ob (b) eine strukturelle Überlegenheit des nordischen Sozialsystems vorliegt.
Keywords: D61; D63; 330; equity; efficiency; tradeoff; welfare states; Soziale Gerechtigkeit; Verteilungsgerechtigkeit; Wirtschaftliche Effizienz; Sozialstaat; Nordeuropa; Europa